Bibliometric Analysis of Mobile Learning Research Trends Over the Last Decade - Erna Handayani (Journal of Research in Mathematics, Science, and Technology Education, 2024)
The use of mobile devices in learning is increasing, allowing students to access learning resources. In the ever-growing digital era, mobile learning not only offers innovative learning alternatives but also shapes the future of education. This study provides a comprehensive bibliometric analysis of 8352 articles on mobile learning in higher education from 2002 to 2023. With the help of VOSViewer, the researcher can explore complex relationships between scientific information, gain deep insights into specific subject areas, and make decisions supported by powerful bibliometric analysis. Key findings reveal a peak in 2019 with 673 publications, and the most cited work is “Current Status, Opportunities And Challenges Of Augmented Reality In Education” by Wu et al. (2013) with 1285 citations. Prolific authors include Hwang, Huang, Ogata, and Looi. Productive sources are ACM International Conference Proceedings Series and journals like International Journal Of Mobile Learning And Organization. Institutions like National Taiwan University and countries like ChinaUnited States, and Taiwan lead in productivity. Top keywords include “mobile learning,” “e-learning,” and “students,” offering insights for future research planning